Ultracold gases and quantum information c - n; Miniatura, C. (Christian) (Oxford : Oxford University Press, 2011)
Since 1951, the prestigious Les Houches summer school has given rigorous graduate programmes in France. In July 2009, the first Les Houches school outside Europe took place in Singapore. This volume gathers the lectures conducted at the four-week school focused on two exciting key topics: quantum information science and ultracold atomic physics.
"This extraordinary session was organized in Singapore ... at the Nanyang Technological University (NTU)."--Pref.
Description based on print version record.
Includes bibliographical references.
Keywords: Quantum theory -- Congresses; Quantum communication -- Congresses; Cold gases -- Congresses; Cooling -- Congresses